Sosialisasi Strategi Menarik Minat Konsumen Untuk Membeli Produk Hasil UMKM - Dede Suleman; Sabil; Ida Zuniarti; Sri Rusiyati (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2021)
This activity aims to provide knowledge about the importance of understanding consumers in this new era because in the sales process in the era and the COVID-19 pandemic, consumer behavior will definitely change. Therefore, the activity with the theme "Strategy to attract consumers to buy UMKM products" is expected to be a solution for UMKM in which the material presented includes the characteristics of consumers and also how to techniques to make consumers feel like buying products produced by UMKM. it is still difficult to be able to market the products they produce and this affects the income level of UMKM actors. At the end of these community service activities, we evaluate by giving questionnaires with respondents to see the percentage of participants' satisfaction levels during community service activities and to measure quantitatively the percentage of influence and impact after completing the implementation of service activities Some of the strategies shared in this socialization are new methods that UMKM actors can use to adapt in the marketing era n new. And it is hoped that it can change the mindset of UMKM actors in making the right marketing strategy in order to increase sales.